2012
DOI: 10.3233/jad-2012-120271
|View full text |Cite
|
Sign up to set email alerts
|

A Rating Scale for Gait Evaluation in Cognitive Deterioration (RSGE-CD): Validation Study

Abstract: A relationship between decline in mobility and walking performance and cognitive impairment exists in the elderly. Therefore, clinical assessment of gait and mobility may be relevant for diagnostic and therapeutic purposes. However, the rating scales used for evaluation of gait disorder in the context of cognitive deterioration were not designed or validated for that setting. The present study was aimed at checking the clinimetric properties of the Rating Scale for Gait Evaluation in Cognitive Deterioration (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…A study in individuals with probable AD used the Rating Scale for Gait Evaluation in Cognitive Deterioration [ 49 ] to assess gait dysfunction. It was reported that less gray matter volume in clusters in the bilateral primary motor cortices, bilateral medial cingulate gyrus, bilateral insula, and bilateral anterior cerebellum indicated poorer gait [ 50 ] (see Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in individuals with probable AD used the Rating Scale for Gait Evaluation in Cognitive Deterioration [ 49 ] to assess gait dysfunction. It was reported that less gray matter volume in clusters in the bilateral primary motor cortices, bilateral medial cingulate gyrus, bilateral insula, and bilateral anterior cerebellum indicated poorer gait [ 50 ] (see Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Motor tests that incorporate gait, such as gait-cognitive dual tasking, and the timed up-and-go test, were related to degeneration of the primary motor cortex and temporal lobe [ 34, 39, 41 ], as well as degeneration and activation changes of the default mode network (dual tasking) [ 45 ], and less frontal, temporal, and cerebellar volume [ 55 ], periventricular WML [ 43, 56 ], and amyloid deposition in the precuneus and cingulum [ 47 ]. Gait disorders in AD were related to volume loss of motor brain regions such as the primary motor cortex and the cerebellum [ 49 ], subcortical and periventricular WML [ 52 ], and microstructural white matter changes of several white matter projections, including the corticospinal tract [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both were deemed feasible to assess in people with advanced dementia. Clinically, they can be evaluated by observation and rated based on degree of assistance required as in the Rating Scale for Gait Evaluation–Cognitive Deterioration [6,20]. Wheeled mobility was not rated highly as a factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…29 Neuropsychiatric variables: the neuropsychiatric inventory 30 was utilized for the evaluation of neuropsychiatric symptoms. Motor variables: parkinsonism was evaluated using the motor evaluation scale of the Scales for Outcomes in Parkinson’s Disease (SCOPA-Motor), 31 and gait was assessed using the Rating Scale for Gait Evaluation in Cognitive Deterioration (RSGE-CD). 32 Other dementia-related variables: disease duration, memory failure, and falls at symptom onset were obtained from medical records and family interview. Severity of dementia was rated following the Global Deterioration Scale 33 and the Clinical Dementia Rating Scale, sum of boxes score.…”
Section: Methodsmentioning
confidence: 99%
“…Motor variables: parkinsonism was evaluated using the motor evaluation scale of the Scales for Outcomes in Parkinson’s Disease (SCOPA-Motor), 31 and gait was assessed using the Rating Scale for Gait Evaluation in Cognitive Deterioration (RSGE-CD). 32…”
Section: Methodsmentioning
confidence: 99%